Asymmetric dimethylarginine compartmental behavior during high-flux hemodialysis. Issue 1 (1st January 2020) - Du, Qiuna; Gao, Jiayuan; Lu, Renhua; Jin, Yun; Zou, Yanfang; Yu, Chen; Yan, Yucheng
Abstract: Aim: The accumulation of uremic toxins, such as asymmetric dimethylarginine (ADMA), has emerged as one of the major cardiovascular disease-related risk factors in patients with end-stage renal disease (ESRD). Based on the low molecular weight of ADMA, hemodialysis (HD) should theoretically effectively remove ADMA. In this study, we investigated the clearance behavior of ADMA during high-flux HD. Methods: Eight HD patients without residual renal function were included. Blood samples were collected at 0, 30, 60, 120 and 240 min after dialysis started, as well as 1 h and 48 h after dialysis. ADMA level was detected by HPLC-MS/MS. Herein, the ADMA level in blood cells and the ADMA protein binding rate were measured. Accordingly, the dialyzer extraction ratio was also determined. Results: The reduction ratio (RR) of ADMA (corrected for hemoconcentration) was significantly lower, at only 37.21 ± 6.44%, than that of urea and creatinine ( p < .05). Interestingly, its clearance from plasma was precipitous early in dialysis and became slowly from 60 to 240 min. Additionally, a greater inlet erythrocyte than plasma concentration was found for ADMA. The dialyzer extraction ratio was comparable between ADMA and creatinine or urea (83 ± 5% for ADMA vs. 84 ± 3% and 88 ± 2% for creatinine and urea, respectively; both p >.05). Urea and creatinine had a slight rebound ratio of less than 10% at 1 h after the completion of HD. In contrast, considerable rebound of approximately 30% was detected in ADMA. Conclusion: This study suggests that ADMA may present a multicompartmental distribution that cannot be representatively reflected by the urea kinetics model.